Assessing the effects of empowerment and emotions on job satisfaction in hotel service environments - Abdul Aziz, Yuhanis; Ennew, Christine (Universiti Putra Malaysia Press, 2013)
While empowerment has been encouraged in the hotel industry, a basic understanding on the possible relationship between empowerment and positive and negative emotions has yet to emerge. Evidence on the effects of empowerment and positive and negative emotions on job satisfaction is also limited. Therefore, the objectives of the study are threefold: to empirically investigate the relationship of empowerment on both positive and negative emotions and job satisfaction, to test whether the positive and negative emotions impose effect on employee’s job satisfaction and to examine the effect of individual empowerment components (task meaningfulness and freedom to perform) on job satisfaction. The approach of the study is based on questionnaires distributed to the frontline hotel employees in Malaysia. It was found that empowerment has a significant positive relationship with positive emotions and a negative relationship with negative emotions. The results also indicate that both empowerment and positive emotions have a significant influence on employee’s job satisfaction. Moreover, as hypothesized, the results support the negative relationship between negative emotions and job satisfaction. Another noteworthy finding was that, the effect of task meaningfulness on job satisfaction was significantly higher than freedom to perform. It is significant that managers should consider employing different forms of empowerment in order to maximize employee’s potential. The management must play an important role in monitoring employee’s emotions at work.